Determination of the soil water repellency of the Mediterranean climate by the use of the mini disk infiltrometer. Case of the micro basin of Tifiles, Tenes, Algeria. - Kessaissia, Abderrahmane; Mazour, Mohamed (Comunicata Scientiae, 2019)
The soil repellency is one of some soil propriety that can be use to indicate the quality of the soil and give a number of information for the soil conservation and the water management. This study show an example of the determination of this parameter in three sites (forest site, after fire forest site and mixed site) by the use of the mini disk infiltrometer test (MDIT) in the small watershed of wadi Tifiles situated in the North West of Algeria that is characterized by a Mediterranean climate. The result show that the water repellency affect namely the after fire forest site which can be equal to 100% of the measured sample flowed by the mixed soil by 93% and the forest site by 80%.